Medieval churches in Scania - Sundnér, Barbro (Lund University, 2015)
The question of how building materials and construction techniques changed over time in the medieval stone church building was tested on a small number of churches in Scania (Swedish: Skåne) on two separate occasions in the 1980s (Sundnér 1986, 1989). The results showed chronological changes both as to what rock types was chosen, how they were cut and how the masonry was done.

When looking at raw materials that could be used for construction it is clear that Scania represents an area of ​​ physical geographic diversity. However, it was possible to see that during the earlier middle ages primarily local rock types were chosen. Long distance transportation of building material was only done occasionally. Example of this can be seen in the first stone constructions during the 11th century with Dalby abbey and the oldest parts of the Cathedral of Lund (Löfvendahl and Sundnér 1997 Sundnér 1995, 2000, 2012).

During the 12th century the sandstone from Höör in central Scania was used as worked stone over a wider geographic area. Primarily it was used in portals and baptismal fonts. However, from the 13th century onward bricks became more and more used as building material. An extensive building of vaults required and resulted in a large production increase of bricks. The bricks also came to replace natural stone into portals and ornaments when the walls became built of field stones. Furthermore, the technique for masonry also changed, which can be seen as the stones were no longer laid in courses. Architectural changes of various kinds are also observed and recorded.

In total there are 283 fully or partially preserved medieval churches in the countryside in Scania. Of these churches 245 are included in the inventory. Six churches (Östra Strö, Östra Hoby, Munka Ljungby, Vallkärra, Skurup and Vinslövs churches) that lack preserved naves have nevertheless been included since there are other parts of the buildings that were interesting in this context.

Purpose:

To examine how building materials and construction techniques changed in the medieval stone church building in Skåne.

Part A: Register of data relating to the whole Church. The information is collected through measurements and observations.

Frågan om hur byggnadsmaterial och byggnadsteknik förändrades i det medeltida stenkyrkobyggandet prövades på ett mindre antal skånska kyrkor vid två olika tillfällen på 1980-talet (Sundnér 1986, 1989). Resultatet visade kronologiska förändringar både beträffande vilka bergarter man valde, hur man bearbetade stenarna och hur man murade.

Eftersom Skåne representerar ett område med skilda naturgeografiska förutsättningar, inte minst när det gäller förekomst av råvaror till byggandet, var det möjligt att se att man under den äldre medeltiden huvudsakligen valde lokala bergarter. Det var bara i undantagsfall, som i det första stenbyggandet under 1000-talet med Dalby kungskyrka och de äldsta delarna av Lunds domkyrka som man valde att transportera byggnadssten längre sträckor (Löfvendahl och Sundnér 1997, Sundnér 1995, 2000, 2012). Under loppet av 1100-talet kom dock sandstenen från Höör i mellersta Skåne att få en större spridning som bearbetad sten främst i portaler och dopfuntar.

Från 1200-talet blev tegel alltmer använt som byggnadsmaterial och fick framför allt under 1400-talet en stor produktionsökning främst för omfattande valvslagning. Teglet kom också att ersätta naturstenen i portaler och utsmyckningar när murarna byggdes av markstenar. Dessutom ändrades murningstekniken genom att stenarna inte längre lades i jämna lager. Även arkitektoniska förändringar av skilda slag är iakttagbara och har därför på olika sätt registrerats, bland annat genom utvecklingsplaner.

Totalt finns 283 helt eller delvis bevarade medeltidskyrkor på landsbygden i Skåne, av dessa ingår 245 kyrkor i inventeringen. Sex kyrkor (Östra Strö, Östra Hoby, Munka Ljungby, Vallkärra, Skurup och Vinslövs kyrkor) som saknar bevarat långhus har ändå tagits med därför att det fanns andra byggnadsdelar som var intressanta i sammanhanget.

Syfte:

Att undersöka hur byggnadsmaterial och byggnadsteknik förändrades i det medeltida stenkyrkobyggandet i Skåne.

Del A: Register över uppgifter som rör hela kyrkan. Informationen är insamlad genom mätningar och observationer.
Medeltida kyrkor i Skåne
Keywords: Middle Ages; medeltid; archaeology and history; arkeologi och historia; History and Archaeology; Historia och arkeologi; History; Historia; Technology and Environmental History; Teknik- och miljöhistoria; Architecture; Arkitektur